Artificial intelligence trends for data analytics using machine learning and deep learning approaches - Gayathri Devi, K. G.; Rath, Mamata; Dieu, Nguyen Thi (Boca Raton, FL : CRC Press, 2021)
"This book focuses on the implementation of various elementary and advanced approaches in AI that can be used in various domains to solve real-time decision-making problems"--
An artificial intelligence system based based power estimation method for CMOS VLSI circuit / Dr. Govindaraj Vellingiri -- Awareness alert and information analysis in social media networking using usage analysis negotiable approach / Dr. M. Alamelu -- Object detection and tracking in video using deep learning techniques : A review / Dhivya Praba R, Kavitha K.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Industrial applications; Machine learning -- Industrial applications; Diagnosis -- Data processing; COMPUTERS / Computer Vision & Pattern Recognition; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Manufacturing